1988
DOI: 10.1109/50.7885
|View full text |Cite
|
Sign up to set email alerts
|

Bottom shape control of optical fiber soot preform by modified VAD method

Abstract: The bottom shape control of optical fiber soot preform by a modified VAD method is proposed to realize the indirect control of the refractive index profile exponent during soot deposition. This proposal is based on the discovery of a close correlation between the refractive index profile exponent and the bottom shape profile exponent of the soot preform. Diameter and refractive index profile fluctuations of the preform with control and without control are analyzed. In the case of no control, these fluctuations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…In the past, the experimental studies had found that the axial fluctuations of refractive index in silica glass could be greatly reduced by adjusting the substrate location to keep the deposition surface shape unchanged. 4,5 Similarly, Santos et al 6 reported that the stress birefringence of silica glass is smaller than 2 nm/cm when a suitable deposition surface shape is used. The temperature gradient in synthetic glass during the annealing is crucial to affect the refractive index uniformity of glass.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the past, the experimental studies had found that the axial fluctuations of refractive index in silica glass could be greatly reduced by adjusting the substrate location to keep the deposition surface shape unchanged. 4,5 Similarly, Santos et al 6 reported that the stress birefringence of silica glass is smaller than 2 nm/cm when a suitable deposition surface shape is used. The temperature gradient in synthetic glass during the annealing is crucial to affect the refractive index uniformity of glass.…”
Section: Introductionmentioning
confidence: 97%
“…Considering the variations of deposition surface shape resulted from the changes of operating conditions such as the flow rate of SiCl 4 and its injecting position, the effects of deposition surface shape on glass quality should be further investigated. In the past, the experimental studies had found that the axial fluctuations of refractive index in silica glass could be greatly reduced by adjusting the substrate location to keep the deposition surface shape unchanged . Similarly, Santos et al reported that the stress birefringence of silica glass is smaller than 2 nm/cm when a suitable deposition surface shape is used.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 This relationship was determined through an approximation of the shape of porous preform deposition surface and the corresponding refractive index distribution by an exponential function. For a parabolic refractive index, Chida et al have obtained that the best porous preform deposition surface profile ͑␣͒ must be about 1.5, while Imoto et al have obtained ␣ values in the 2.5-3.0 range.…”
Section: Introductionmentioning
confidence: 99%
“…The accuracy of the germanium concentration depends on the measuring accuracy of the surface temperature of porous preform, which can be influenced by flame fluorescence. Imoto et al [11] introduced an alternative method to control the doping profile by controlling the shape of the preform bottom profile, which was parameterized using the α parameter, the power law index profile that best fits the preform bottom profile. The control is performed by a feedback system that acts in the pulled-up velocity preform according to its bottom shape (α).…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, the present research presents a technique to fabricate VAD preforms with triangular and standard graded index profiles, based on the correlation between the germanium doping profile and the deposition surface shape of VAD preforms [11], which was possible to perform through the correlation and the parameterization of preform deposition surface by 0733-8724/$20.00 © 2006 IEEE α and h parameters. It was then possible to establish the type of doping profile, such as graded or triangular, before starting the preform deposition process and to detect variations of the axial uniformity of the germanium doping profile in the preform during the early stage of fabrication.…”
Section: Introductionmentioning
confidence: 99%